Hyperglycemia in Pregnancy: Recent Diagnostic Criteria and Pharmacologic Treatment for Glycemic Contro - John M.F. Adam; Fabiola M.S. Adam (Indonesian Socety of Obstetrics and Gynecology, 2012)
Hyperglycemia in pregnancy, or formerly known as gestational diabetesmellitus, is defined as carbohydrate intolerance of variable severitywith onset or first recognition during pregnancy. The classicalscreening and diagnosis of hyperglycemia in pregnancy is the twostepsscreening, consists of 50 gram glucose load and follow by 3-hour 100 gram oral glucose test for those who were screening positive.The diagnosis of hyperglycemia in pregnancy is made if at leasttwo abnormal elevated values i.e. fasting > 95 mg/dl, 1 hour > 180mg/dl. 2 hour > 155 mg/dl, and 3 hour > 140 mg/dl.The International Association of Diabetes and Pregnancy StudyGroups Consensus Panel (IADPSG) in 2010 and the American DiabetesAssociation in 2011 change the method of screening and diagnosticcriteria. In the new method of screening all pregnant woman,not only the high risk group, should be screened using oral glucosetolerance test with 75 gram of glucose. The new diagnosis criterianeed only one abnormal plasma glucose value i.e. fasting > 92 mg/dlor 1 hour > 180 mg/dl, or 2 hour > 153 mg/dl. There is debate whichcriteria should be used universally, since the new criteria will increasethe prevalence of hyperglycemia in pregnancy.In most diabetic clinics, especially in the North America, besidesmedical nutrition therapy, insulin remains the mainstay of treatmentfor this patient. However, for those women who cannot afford insulinor do not wish to take insulin, glibenclamide and metformin, maybe offered as an alternative. Most experts will prefer to use metformin,since it does not increase body weight and also has an insulinsensitivity effect.Keywords: hyperglycemia in pregnancy, IADPSG criteria, pharmacologictreatment